Harnessing slow event-related fMRI to investigate trial-level brain-behavior relationships during object identification - Gotts, Stephen J.; Gilmore, Adrian W.; Martin, Alex (Frontiers in Human Neuroscience, 2024)
Understanding brain-behavior relationships is the core goal of cognitive neuroscience. However, these relationships—especially those related to complex cognitive and psychopathological behaviors—have recently been shown to suffer from very small effect sizes (0.1 or less), requiring potentially thousands of participants to yield robust findings. Here, we focus on a much more optimistic case utilizing task-based fMRI and a multi-echo acquisition with trial-level brain-behavior associations measured within participant. In a visual object identification task for which the behavioral measure is response time (RT), we show that while trial-level associations between BOLD and RT can similarly suffer from weak effect sizes, converting these associations to their corresponding group-level effects can yield robust peak effect sizes (Cohen’s d = 1.0 or larger). Multi-echo denoising (Multi-Echo ICA or ME-ICA) yields larger effects than optimally combined multi-echo with no denoising, which is in turn an improvement over standard single-echo acquisition. While estimating these brain-behavior relationships benefits from the inclusion of a large number of trials per participant, even a modest number of trials (20–30 or more) yields robust group-level effect sizes, with replicable effects obtainable with relatively standard sample sizes (N = 20–30 participants per sample).